2013
DOI: 10.7150/ijms.5185
|View full text |Cite
|
Sign up to set email alerts
|

Increased Co-Expression of Macrophage Migration Inhibitory Factor and Matrix Metalloproteinase 9 Is Associated with Tumor Recurrence of Meningioma

Abstract: Background and Objective: We detected the expression of MIF and matrix metalloproteinase 9 (MMP9) in meningiomas to determine whether they are valuable recurrence predictor for meningioma.Methods: 67 cases of meningiomas, including 57 benign tumors (WHO grade I) and 10 non-benign tumors (WHO grade II and III), were collected, and expression of MIF and MMP9 in tissue microarray was evaluated immunohistochemically. The correlations between immunostainings and clinicopathological parameters, as well as the follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
3
10
0
Order By: Relevance
“…The data shown here indicate that tissue MMP-9 expression is significantly increased in atypical meningiomas compared to lower grade specimens, and is positively correlated with Ki-67 index levels. These results are in keeping with the data of other authors who observed a deeper expression of MMP-9 in high-grade meningiomas, accompanied by a positive correlation with tumor invasion and recurrence [ 29 – 32 ].…”
Section: Discussionsupporting
confidence: 92%
“…The data shown here indicate that tissue MMP-9 expression is significantly increased in atypical meningiomas compared to lower grade specimens, and is positively correlated with Ki-67 index levels. These results are in keeping with the data of other authors who observed a deeper expression of MMP-9 in high-grade meningiomas, accompanied by a positive correlation with tumor invasion and recurrence [ 29 – 32 ].…”
Section: Discussionsupporting
confidence: 92%
“…Huang et al detected the expressions of matrix metalloproteinase 9 (MMP-9) in meningiomas to determine whether they are a valuable recurrence predictor for meningioma. Increased expressions of MMP-9 were significantly associated with a tumor's microvessel density (MVD), in relation to tumor invasion and tumor recurrence, concluding that together with histological grade increased MMP-9 expression in a tumor might be a valuable predictor for recurrence, especially for benign meningiomas [ 12 ]. Also, Kwon et al showed high MMP-9 expression in clear cell and rhabdoid meningiomas, and high expression of matrix metalloproteinase 9 was associated with tumor recurrence and local invasion at the time of diagnosis [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…In brain tumors, mainly in gliomas, MMPs have been well studied according to brain glioma invasion. Recently, limited data suggest that the expression of matrix metalloproteinases (MMPs) may be related with the presence of PTBE in meningiomas [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study also demonstrated that the deficiency of DEP-1 promotes the progression of meningioma ( 56 ). A separate study demonstrated that the expression levels of tissue inhibitor of metalloproteinases-1 (TIMP-1) in invasive meningioma is significantly lower than that in non-invasive meningioma, possibly related to the inhibition of MMP-9 activity by TIMP-1 ( 57 ). The expression of A-kinase anchor protein 12 (AKAP12) increased in actively migrating cells, believed to play an important role in actin dynamics and actin filament-based migration ( 58 ).…”
Section: Molecular Mechanisms Of Change In Biological Behaviormentioning
confidence: 99%